Landslide Risk Assessment of the Patlekhet Landslide in Myagdi District, Nepal - Adhikari, Basanta Raj; Nidal, Naresh; Yadav, Bhupendra Kumar; Awasthi, Surendra (Journal of the Institute of Engineering, 2018)
Abstract: Nepal Himalaya is one of the most active mountain belts with several kilometers of relief which is very prone to catastrophic mass failure and this region encounter the problem of landslide almost every year during monsoon period causing large scale of devastation. Most of the landslides are caused by river bank erosion, monsoon and earthquakes. Patlekhet landslide, Myagdi district represents the vulnerable condition of the hilly region and therefore it is chosen for study. Hydro-meteorological analysis of the landslide including estimation of the physical characteristics of the landslide and different parameter were used for the study. The Thiessen polygon and arithmetic average methods are used for rainfall analysis of the landslide and high flood level is estimated at the toe of the landslide. The risk is calculated by assessing the vulnerability of different exposure elements such as population, households, agricultural land and water supply through the use of quantitative tools and techniques. It is clear that the landslide was triggered by heavy rainfall and toe cutting by Raghu Ghat Khola. Around fourteen percent households’ lie in the high risk zone and others are in moderate and low risk zone. The level of risk is changing every year with increasing number of population and continuous movement of landslide. Journal of the Institute of Engineering, 2017, 13(1): 78-89